2023
DOI: 10.1021/acs.macromol.3c00220
|View full text |Cite
|
Sign up to set email alerts
|

Biobased, Reprocessable Non-isocyanate Polythiourethane Networks with Thionourethane and Disulfide Cross-Links: Comparison with Polyhydroxyurethane Network Analogues

Abstract: Here, we report the first study of the reprocessability and properties of non-isocyanate polythiourethane (NIPTU) networks in which the cross-links are of two types, thionourethane and disulfide, the latter obtained by auto-oxidation of pendant thiol groups. Our two NIPTU networks are biowaste based because starting materials can be derived from cashew nutshells or rice husks. We use dynamic mechanical analysis, tensile testing, and water sorption studies to compare our NIPTU networks with structurally analogo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 135 publications
(278 reference statements)
2
29
0
Order By: Relevance
“…We attempted to post-cure our materials at 120 °C for 4 h, but it only led to a marginal increase in cyclic carbonate conversion. Indeed, a previous study by Chen et al employing NC-514 to synthesize bulk PHU networks also shows incomplete conversion even after extended post-curing at 80 °C for 3 days . Nevertheless, swelling results show a sufficient cross-linking degree in the foam materials.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…We attempted to post-cure our materials at 120 °C for 4 h, but it only led to a marginal increase in cyclic carbonate conversion. Indeed, a previous study by Chen et al employing NC-514 to synthesize bulk PHU networks also shows incomplete conversion even after extended post-curing at 80 °C for 3 days . Nevertheless, swelling results show a sufficient cross-linking degree in the foam materials.…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, a previous study by Chen et al employing NC-514 to synthesize bulk PHU networks also shows incomplete conversion even after extended post-curing at 80 °C for 3 days. 48 Nevertheless, swelling results show a sufficient cross-linking degree in the foam materials. With the successful syntheses of NC-514 foams in this study and nonbio-based foams in our previous study, 28 we have demonstrated that our rheological strategy applies in various situations and for different monomer structures to construct NIPU foams and that it shows promise for significantly accelerating the discovery of NIPU foam materials.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations